Mister Exam

Other calculators


(3^n-1)/6^n

Sum of series (3^n-1)/6^n



=

The solution

You have entered [src]
  oo        
____        
\   `       
 \     n    
  \   3  - 1
   )  ------
  /      n  
 /      6   
/___,       
n = 0       
$$\sum_{n=0}^{\infty} \frac{3^{n} - 1}{6^{n}}$$
Sum((3^n - 1)/6^n, (n, 0, oo))
The radius of convergence of the power series
Given number:
$$\frac{3^{n} - 1}{6^{n}}$$
It is a series of species
$$a_{n} \left(c x - x_{0}\right)^{d n}$$
- power series.
The radius of convergence of a power series can be calculated by the formula:
$$R^{d} = \frac{x_{0} + \lim_{n \to \infty} \left|{\frac{a_{n}}{a_{n + 1}}}\right|}{c}$$
In this case
$$a_{n} = 3^{n} - 1$$
and
$$x_{0} = -6$$
,
$$d = -1$$
,
$$c = 0$$
then
$$\frac{1}{R} = \tilde{\infty} \left(-6 + \lim_{n \to \infty} \left|{\frac{3^{n} - 1}{3^{n + 1} - 1}}\right|\right)$$
Let's take the limit
we find
False

False

$$R = 0$$
The rate of convergence of the power series
The answer [src]
4/5
$$\frac{4}{5}$$
4/5
Numerical answer [src]
0.800000000000000000000000000000
0.800000000000000000000000000000
The graph
Sum of series (3^n-1)/6^n

    Examples of finding the sum of a series